Clinical manifestations of oculodentodigital dysplasia - Gurusamy Kayalvizhi; Balaji Subramaniyan; Gurusamy Suganya (Wolters Kluwer Medknow Publications, 2014)
Oculodentodigital dysplasia (ODDD) is a multisystem congenital disorder characterized by abnormal facial development, deformed limbs and dentition. This report describes a rare incidence of ODDD-linked dermatological, cardiac, dental, and neurologic manifestations noted in an Indian child patient.